2017
DOI: 10.1055/s-0037-1598243
|View full text |Cite
|
Sign up to set email alerts
|

Air and Bone Conduction Frequency-specific Auditory Brainstem Response in Children with Agenesis of the External Auditory Canal

Abstract: Introduction  The tone-evoked auditory brainstem responses (tone-ABR) enable the differential diagnosis in the evaluation of children until 12 months of age, including those with external and/or middle ear malformations. The use of auditory stimuli with frequency specificity by air and bone conduction allows characterization of hearing profile. Objective  The objective of our study was to compare the results obtained in tone-ABR by air and bone conduction in children until 12 months, with agenesis of the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Electrophysiology studies in children with ear malformations 14 , 23 , 24 , 25 demonstrated higher thresholds through air conduction assessment than bone conduction, which characterizes conductive hearing loss, commonly associated with ear malformations. The electrophysiological thresholds by AC and BC allow the characterization of the audiological profile, which shows a good correlation with the behavioral audiological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiology studies in children with ear malformations 14 , 23 , 24 , 25 demonstrated higher thresholds through air conduction assessment than bone conduction, which characterizes conductive hearing loss, commonly associated with ear malformations. The electrophysiological thresholds by AC and BC allow the characterization of the audiological profile, which shows a good correlation with the behavioral audiological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative procedure, behavioral audiometry was performed for 8 patients (12 ears), while 2 other patients, aged 10 and 9 years, were still unable to undergo behavioral audiometry. In these two patients, bone conduction ABR, allowing the identification of the type and the degree of conduction hearing loss, was performed to assess the cochlear integrity [29]. Due to psychosocial problems, the two subjects could not complete another audiological test session.…”
Section: Discussionmentioning
confidence: 99%
“…No grupo controle, os limiares médios obtidos por via aérea em 500 Hz (26,6 dBnNA) e 2000 Hz (21,5 dBnNA) foram semelhantes aos obtidos em estudos na literatura (21,23) e discretamente superiores aos alcançados em outro estudo (18) . Na frequência de 2000 Hz, os limiares foram melhores do que os obtidos em estudos brasileiros (20,24) realizados com o mesmo equipamento. Essas diferenças devem-se ao fato de os estudos estabelecerem o nível mínimo de resposta, finalizando o exame ao atingir 30 dBnNA.…”
Section: Discussionunclassified
“…Provavelmente, esse fato ocorreu também em razão das alterações de rigidez sofridas na orelha média (1,22) . Efetivamente, limiares eletrofisiológicos mais elevados em 500 Hz por via aérea em crianças com e sem alterações condutivas já haviam sido encontrados na literatura (2,20,21,24) . Tal resultado também pode ser justificado pela dificuldade de obtenção e visualização da onda V em 500 Hz, em fracas intensidades, visto que frequências baixas sofrem maior contaminação pelo ruído e precisam de mais tempo para atingir o ápice da cóclea e produzir respostas (25) .…”
Section: Discussionunclassified